2015
DOI: 10.1017/s1368980015000920
|View full text |Cite
|
Sign up to set email alerts
|

Community-based educational intervention improved the diversity of complementary diets in western Kenya: results from a randomized controlled trial

Abstract: Objective: Lack of diversity is a major factor contributing to inadequate nutrient intakes among children during the complementary feeding period in many rural areas in developing countries. This has been attributed to inadequate feeding practices and nutrition knowledge among their caregivers. The aim of the present study was to assess the effect of an educational intervention on children's dietary diversity and nutrition knowledge of caregivers. Design: Cluster randomization was applied and twenty matched vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
129
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(150 citation statements)
references
References 39 publications
16
129
4
1
Order By: Relevance
“…Contrary to findings from Waswa et al. (), this study and others have shown that nutrition knowledge of caregivers positively predicts adequate dietary intakes of infants (Dewey and Adu‐Afarwuah ; Inayati et al. ).…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to findings from Waswa et al. (), this study and others have shown that nutrition knowledge of caregivers positively predicts adequate dietary intakes of infants (Dewey and Adu‐Afarwuah ; Inayati et al. ).…”
Section: Discussioncontrasting
confidence: 99%
“…Here, the respondents improved their practical knowledge, in terms of being better able to name foods rich in the respective nutrients. This is in accordance with studies which showed that practical nutrition knowledge played a greater role in the nutrition outcomes as compared to the education level of the mother [36,37].…”
Section: Discussionsupporting
confidence: 92%
“…For instance, Appoh and Krekling (2005) found that impact of maternal nutritional knowledge on child nutrition status was greater than that of formal education. This is to say that even those caregivers who do not have formal education can still realize better nutritional outcomes for their vs. 51.9%, P < 0.001), the increase in DDS was not associated with the observed increase in maternal nutrition knowledge (Waswa, Jordan, Herrmann, Krawinkel, & Keding, 2015). The authors conclude that effect of the intervention on child dietary diversity was not via an increase in nutrition knowledge of the caregivers per se and that although increased nutrition knowledge is an important factor, on its own, it cannot lead to changes in behaviours.…”
Section: Discussionmentioning
confidence: 88%
“…In a randomized‐cluster controlled trial on the effect of nutrition education focusing on the utilization of local agro‐biodiversity in improving the diversity of children's complementary diets and nutrition knowledge of caregivers, the researchers noted that although a significantly higher proportion of children in the intervention group compared with those in the control group achieved minimum dietary diversity (87.3% vs. 55.7%, P < 0.001); minimum meal frequency (98.8% vs. 88.6%, P = 0.019); and minimum acceptable diet (87.8% vs. 51.9%, P < 0.001), the increase in DDS was not associated with the observed increase in maternal nutrition knowledge (Waswa, Jordan, Herrmann, Krawinkel, & Keding, ). The authors conclude that effect of the intervention on child dietary diversity was not via an increase in nutrition knowledge of the caregivers per se and that although increased nutrition knowledge is an important factor, on its own, it cannot lead to changes in behaviours.…”
Section: Discussionmentioning
confidence: 99%